2009
DOI: 10.1007/s00404-009-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy on glucose and lipid profiles and on cardiovascular risk parameters in postmenopausal women

Abstract: In response to 6 months of HRT, there was an increase in weight, BMI, and waist/hip ratio as known cardiovascular risk factors, but no significant impact on lipid profile and glucose metabolism could have been clearly demonstrated. A mixed effect profile of HRT on the state of inflammation (increase in CRP and homocysteine, decrease in fibrinogen) was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In two studies performed in postmenopausal women and young healthy women respectively, the use of low-dose combined OCs has increased homocysteine levels. 39,40 EE-DRSP monotherapy for 6 months did not show an impact on homocysteine levels in lean and obese PCOS patients. 22 A study by Cagnacci et al investigated the treatment with EE-CA and found lower homocysteine levels, while EE-DSG had no effect on homocysteine level in the same study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In two studies performed in postmenopausal women and young healthy women respectively, the use of low-dose combined OCs has increased homocysteine levels. 39,40 EE-DRSP monotherapy for 6 months did not show an impact on homocysteine levels in lean and obese PCOS patients. 22 A study by Cagnacci et al investigated the treatment with EE-CA and found lower homocysteine levels, while EE-DSG had no effect on homocysteine level in the same study.…”
Section: Discussionmentioning
confidence: 76%
“…The influence of OCs on homocysteine levels has been investigated but the results are less conclusive than CRP studies. In two studies performed in postmenopausal women and young healthy women respectively, the use of low‐dose combined OCs has increased homocysteine levels . EE‐DRSP monotherapy for 6 months did not show an impact on homocysteine levels in lean and obese PCOS patients .…”
Section: Discussionmentioning
confidence: 89%
“…In many studies, favourable effect of long -term hormonal replacement therapy on angiotensin -converting enzyme activity and bradykinin in postmenopausal women was found [3,7,21]. The results of studies performed by many authors should be the inspiration to supplementation of transdermal HRT in the prophylaxis of cardiovascular events in postmenopausal women [4,11,13,19,21,28].…”
Section: Discussionmentioning
confidence: 98%
“…In postmenopausal women the increase of total cholesterol (T-CH), low density lipoprotein -cholesterol (LDL-CH), triglycerides (TG) and the decrease of high density lipoprotein -cholesterol (HDL-CH) was found [13]. Dyslipidemia is the risk factor of coronary heart disease development, whose incidence in women after 50. is still significantly lower, compared to men, but the prognosis is worse following the deficit of estrogens and the disturbances of hemostatic factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The literature is conflicted as to whether the use of hormone replacement (estrogen alone, estrogen + progestin, oral or non-oral formulations all being pertinent variables) results in lower homocysteine levels or has no effect. 21-24 Whether statins and other cholesterol-lowering agents affect homocysteine levels is also controversial. 25 As their covariate effects are not known definitively, we adjusted for these potential confounders.…”
Section: Commentmentioning
confidence: 99%